Princeton Theological Seminary library (Internet Archive, 2018)
"A digital library of theology and religion : The Internet Archive and Princeton Theological Seminary share in the vision and mission of building a digital library freely accessible to scholars, pastors, and other readers around the globe. To that end, in partnership with the Internet Archive, Princeton Theological Seminary is developing the Theological Commons, a digital library of 78,000+ books and journals on theology and religion, including 28,000+ volumes from the Princeton Theological Seminary Library, digitized by the Internet Archive. y"